2022
DOI: 10.1186/s12957-022-02488-3
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of total proctocolectomy with straight ileoanal anastomosis plus pedicled omental transposition for familial adenomatous polyposis: a preliminary study

Abstract: Purpose To achieve excellent postoperative bowel function in familial adenomatous polyposis (FAP) patients, it is important to reconstruct the digestive tract. The aim of this study is to preliminarily discuss the advantages of total proctocolectomy with straight ileoanal anastomosis (TPC-SIAA) plus pedicled omental transposition for FAP. Methods A retrospective study was carried out in two hospitals analysing data for FAP patients who underwent su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…As for the postoperative low anterior resection syndrome, Qin et al found that TPC with straight ileoanal anastomosis plus pedicled omental transposition for FAP is consistent with intestinal physiology, with good intestinal compliance and anal function tended to be as expected over time. 37 For patients with extensive polyposis in whole colon and lower rectal cancer, anus cannot be preserved, EI is proposed after TPC. Though this surgical approach can prevent CRC completely, it also deteriorates body image with permanent colostomy.…”
Section: Surgical Options For Fapmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the postoperative low anterior resection syndrome, Qin et al found that TPC with straight ileoanal anastomosis plus pedicled omental transposition for FAP is consistent with intestinal physiology, with good intestinal compliance and anal function tended to be as expected over time. 37 For patients with extensive polyposis in whole colon and lower rectal cancer, anus cannot be preserved, EI is proposed after TPC. Though this surgical approach can prevent CRC completely, it also deteriorates body image with permanent colostomy.…”
Section: Surgical Options For Fapmentioning
confidence: 99%
“…As for the postoperative low anterior resection syndrome, Qin et al found that TPC with straight ileoanal anastomosis plus pedicled omental transposition for FAP is consistent with intestinal physiology, with good intestinal compliance and anal function tended to be as expected over time. 37…”
Section: Surgical Options For Fapmentioning
confidence: 99%